An Inventory of Vascular Flora of the Lalmai Hill Area Of Cumilla District, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2022)
In this study, the vascular flora of the Lalmai hill area of the Cumilla district has been thoroughly explored. This study reveals the occurrence of 923 species of vascular plants under 594 genera and 141 families in the study area, which represents 23.75% of the total 3886 plant species reported from Bangladesh until now. About 68.15% of these species are native and 31.85% are exotic to Bangladesh. Pteridophytes are represented by 30 species belonging to 21 genera and 11 families, whilst Gymnosperms are represented by eight species under seven genera and six families. Magnoliopsida (dicotyledons) comprises 661 species, including four subspecies and two varieties, from 429 genera and 96 families, accounting for 71.54% of the vascular flora of the study area. Liliopsida (monocotyledons) represents 225 species under 137 genera and 28 families, making up 24.35% of this flora. In Magnoliopsida, Fabaceae with 55 species is the largest dicot family, followed by Asteraceae, Malvaceae, Euphorbiaceae, Lamiaceae and Rubiaceae. Most of the species of Liliopsida (68%) are represented by the five families viz., Poaceae, Cyperaceae, Araceae and Commelinaceae. Poaceae with 75 species is the largest monocot family, followed by Cyperaceae, Orchidaceae, Araceae and Arecaceae. The genus Cyperus is the largest in the study area. The species Antidesma roxburghii Wall. ex Tul. of Phyllanthaceae is rediscovered in Bangladesh. Most of the Magnoliopsida and Liliopsida are herbs (59.80%), which are followed by trees (21.02%), shrubs (17.23%), and palms (1.41%). About 64.57% of the species are recorded as wild, but a significant percentage (27.41%) is planted and cultivated (8.02%). The majority of the species are found to grow in eight categories of habitat viz., roadside, fallow land, homestead, woodland, garden, scrub jungle, agricultural field and grassland. Eight plant species, listed in the Red Data Book of Bangladesh including six as Data Deficient (DD), one Not Evaluated and one Endangered (EN) species, are harboured in the study area. We strongly recommend the adoption of a master plan for minimizing all major threats to the vegetation and habitats of this area and sustainable development, utilization and conservation of its plant resources.Bangladesh J. Plant Taxon. 29(2): 203-240, 2022 (December)